F60. RELATIONSHIP BETWEEN DAT1 AND DRD4 GENO-TYPES AND NEUROCOGNITIVE TEST PERFORMANCE IN PATIENTS DIAGNOSED WITH ADHD - Unsel-Bolat, Gul; Bolat, Hilmi; Yildirim, Sema; Ozgul, Semiha; Tahillioglu, Akin; Yazici, Kemal Utku; Bolat, Hilmi (Elsevier, 2024)
[Abstract Not Available]
World Congress of Psychiatric Genetics (WCPG) -- OCT 15-19, 2024 -- Singapore, SINGAPORE